Forecasting of Indonesia's Gross Domestic Product Amid Covid-19 Pandemic - Izzah, Nurul (El-Barka Journal of Islamic Economics and Business, 2021)
The Indonesian economy since the first quarter of 2020 has declined. The Covid-19 pandemic has suppressed Indonesia's economic growth. The Ministry of Finance stated that the Indonesian economy in 2020 is estimated to reach minus 1.7 percent to 0.6 percent. The purpose of this study is to determine the prediction of Indonesia's GDP amid Covid-19 pandemic. This type of research is a quantitative study using secondary data with a sample size of 22 samples. The data analysis technique used is the ARIMA method. The results showed stationary data at the second level. Identification of the Bob-Jenkins model selected the ARIMA model (4,2,1). The forecast results show that Indonesia's GDP in the second quarter of 2020 until the second quarter of 2023 will continue to decline. Therefore, policies to promote economic recovery are required. This policy must support the improvement of the health system to reduce the impact of the Covid-19 pandemic on activities and community works. Long-term impacts can be maintained by improving administration, facilitating a more investor-friendly business environment, and increasing budgets to improve education and health facilities.Perekonomian Indonesia sejak triwulan IV-2020 telah mengalami penurunan. Pandemi Covid-19 telah menekan pertumbuhan ekonomi Indonesia. Kementerian Keuangan menyatakan, perekonomian Indonesia pada 2020 diperkirakan mencapai minus 1,7 persen hingga 0,6 persen. Tujuan penelitian ini adalah untuk mengetahui prediksi PDB Indonesia. Jenis penelitian ini adalah kuantitatif dengan menggunakan data sekunder dengan jumlah sampel sebanyak 22 sampel. Teknik analisis data yang digunakan adalah metode ARIMA. Hasil penelitian menunjukkan bahwa data stasioner pada tingkat kedua. Identifikasi model Bob-Jenkins terpilih model ARIMA (4,2,1). Hasil peramalan menunjukkan bahwa PDB Indonesia triwulan II-2020 smpai dengan triwulan II-2023 terus mengalami penurunan. Oleh karena itu, diperlukan kebijakan yang mendorong pemulihan ekonomi. Kebijakan tersebut harus mendukung peningkatan sistem kesehatan untuk mengurangi dampak pandemi Covid-19 pada aktivitas dan pekerjaan masyarakat. Dampak jangka panjang dapat dikurangi dengan perbaikan tata kelola, lingkungan bisnis yang lebih ramah kepada investor dan meningkatkan anggaran untuk memperbaiki fasilitas pendidikan dan kesehatan.